Pengaruh Leverage, Profitabilitas, Sales Growth, terhadap Tax Avoidance: Moderasi Ukuran Perusahaan - Atika Rizky Ramadhani; Fachrurrozie Fachrurrozie (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
Tax is a major source of government revenue; however, tax avoidance remains a significant issue, particularly in the property and real estate sector, which is characterized by high growth and complex financial structures. This study examines the effects of leverage, profitability, and sales growth on tax avoidance, with firm size as a moderating variable. The study employs a quantitative approach, using secondary data from the annual financial statements of property and real estate companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The sample was selected using purposive sampling, and the data were analyzed using panel data regression techniques. Tax avoidance is proxied by the Cash Effective Tax Rate, leverage is measured by the Debt-to-Equity Ratio, profitability is measured by Return on Assets, sales growth is calculated as the annual change in sales, and firm size is measured using the natural logarithm of total assets. The results indicate that leverage and profitability significantly affect tax avoidance, whereas sales growth does not. Firm size is found to moderate the relationship between leverage and tax avoidance as well as between profitability and tax avoidance, but it does not moderate the relationship between sales growth and tax avoidance. The novelty of this study lies in the inclusion of sales growth as an independent variable and the positioning of firm size as a moderating variable within the property and real estate sector during the post-pandemic period. These findings provide practical implications for corporate tax management strategies and offer insights for regulators in strengthening tax supervision based on firm characteristics.